2015
DOI: 10.2298/mpns1510308r
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after bilateral anterior cruciate ligament reconstructions

Abstract: Resuming the same or higher level of sports activitie., after the first reconstruction is one of the preconditions for the same injury of another knee. An athlete looses more than two and a half years of competitions on average. Operations of additional meniscu ruptures do not play a crucial role in restitution of sports activities Although we achieved good operative results, only every seconc athlete with bilateral injury has returned to sports activities withou restrictions after the bilateral anterior cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…Athletes lose 2½ years on average before they can return to competitions. Even though satisfactory results were recorded, only every second athlete with bilateral injury and a previous reconstruction procedure was able to return to competitions fully (45).…”
Section: Hssmentioning
confidence: 96%
“…Athletes lose 2½ years on average before they can return to competitions. Even though satisfactory results were recorded, only every second athlete with bilateral injury and a previous reconstruction procedure was able to return to competitions fully (45).…”
Section: Hssmentioning
confidence: 96%
“…In the literature, the postoperative Lysholm score in the cyclops syndrome ranges between 91.5 and 94.1 points [11,33], while in other surgical procedures used for the elimination of knee adhesions, only 82 points [12]. In our earlier papers [35][36][37][38], this value ranged between 93 and 97 points, which indicated that cyclops lesion is a complication that significantly compromises the average results of ACL reconstruction.…”
Section: Ristić V Et Al Cyclops Syndrome After Acl Reconstructionmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) reconstructions are successful in providing excellent results in about 80 -90% of all performed operations [1][2][3][4][5]. However, the reconstructions sometimes fail, in regard to stability and symptoms that significantly reduce the patient's quality of life [1][2][3][4][5][6]. Incorrect tibial and femoral tunnel placement has been recognized as a common technical error leading to failure [1][2][3].…”
Section: Introductionmentioning
confidence: 99%